The differences about behaviour of providing breast milk’s complementasry food by mother with under two years child stunting and non stunting in Kedungwaringin Health Centre Area - Agustin, Dewi; Fitri Andini, Rizky; Prastiwi, Ikha (Institute Of Computer Science (IOCS), 2024)
Nutrition in the first 1000 days of birth (HPK) is seen as one of the main factors in a child's growth and development, this can influence the stunting status of children during that period. breast milk’s Complementary food (MPASI), which is additional food given to babies after the baby is 6 months old, is given to accompany and complement breast milk. Breast milk must continue to be given to babies, at least until the age of 24 months. This research is aimed at finding out any differences in the pattern of giving MP ASI by mothers to stunting and non-stunting infants in the Kedungwaringin Community Health Center working area. This research is an observational study with a cross sectional approach, with a sample size of 34 respondents. where data on stunting and non-stunting was obtained based on data on the nutritional status of toddlers at the Kedungwaringin Community Health Center, followed by a questionnaire on providing MP ASI to the respondent's mother. The results of this study showed that the inappropriate behavior of giving MP ASI to stunted and non-stunting toddlers was 81.25% and 38.8%, the results of the chi square test showed a p value of 0.017 (< 0.05) There is a significant difference in the behavior of giving breast milk’s complenetary food to stunted and non-stunting toddlers in the Kedungwaringin Community Health Center working area. Suggestion - It is important to carry out education and counseling regarding the behavior of giving complementary food which can be given before the pregnancy period